Agronomic performance of rare hybrids with female restitution in interspecific crosses of commercial cultivar of sugarcane and Saccharum spontaneum L. - Suganya, A; Arulmathi, R; Govindaraj, P; Selvi, A (Journal of Sugarcane Research, 2021)
High compatibility in interspecific crosses among species of Saccharum with peculiar chromosome transmissions in the progeny is well documented. It depends upon the species combination used in the interspecific crosses. Though 2n + n transmission is common in Saccharum officinarum x S. spontaneum, which led to the success of the first man made interspecific commercial hybrid Co 205, it is an uncommon phenomenon with commercial cultivar x S. spontaneum. Recently, 2n+n transmission with female restitution in two hybrids from the crosses of Co 89029 (2n=110) x S. spontaneum (2n =88) and Co 89029 (2n=110) x S. spontaneum (2n = 112) has been identified. These hybrids, 04-2153 with 2n=153 and 04-244, 2n=166 were evaluated for their agronomic characters. Improvement over the female parent was observed for number of millable canes (74.3%), plant height (15.0 % ), cane yield (7.37 %), dry matter production (67.14%), fibre (59.62 %) and pollen fertility (97.16 %) in the hybrid 04-2153 while the hybrid 04-244 had shown considerable improvement over the female parent for number of millable canes (49.85 %), cane yield (25.59 %), pollen fertility (46.83%), dry matter production (34.27) and fibre content (46.15%). Performance of these hybrids and their utilisation in commercial breeding programme are discussed.